Logical fallacy in architectural design studio - Nahith Taha Abdullah; Areej Abdulrazaq Hameed (Sulaimani Journal for Engineering Sciences, 2019)
This paper attempts to shed light on a phenomenon that occurs in the discourse in general which is the logical fallacies, as it tries to project it on architecture criticism that take place inside design studio, as a type of discourse. It adopts an analytical approach considering criticism process as one of its basic elements, to test the main hypothesis which is the possibility of existance of some logical fallacies in criticism directed to students during the conceptual phase of the design process. The paper also tries to clarify the effect of design session time on the nature of these fallacies. The paper finds some of these fallacies vary in numbers types and repetation during the monitering of the design session. It also finds that the progress of sessions decreases the number of fallacies significantly. This paper tries to come out of its results with indicators to refine the academic practice into the field of architecturl design criticism, in the aim of contributing to its improvement and development.